Influence of Temperature on Laminated Glass Performances Assembled with Various Interlayers - M. Novotny (Challenging Glass Conference, 2016)
The increasing demand for use of laminated glass in building facades is the driving force for new interlayers testing and their implementation. Architects’ and engineers’ requests require searching for new solutions and processes of lamination. Intelligent facades, electrochromic windows, integrated photovoltaics, integrated lighting, enhanced solar control, acoustic pollution reduction, wires incorporation, use of special sealants and glues are some of the design drivers of new laminated structures.